Development of cryogenic technology for the production of nano-powders from topinambour using liquid and gaseous nitrogen - Павлюк, Раїса Юріївна; Бессараб, Олександр Семенович; Погарська, Вікторія Вадимівна; Балабай, Катерина Сергіївна; Лосєва, Світлана Михайлівна (Eastern-European Journal of Enterprise Technologies, 2015)
The cryogenic technology for the production of nanopowders from topinambour, which differs from conventional in applying cryogenic "shock" freezing using liquid and gaseous nitrogen, low-temperature fine grinding and freeze drying, allowing not only to preserve all biologically active substances, but also to extract them better from the bound with the biopolymers of nanocomplexes in the free state and to destroy much of the inulin polysaccharide to its individual monomers - fructose was proposed and developed. The technology differs from conventional in the fact that it completely excludes the heat treatment of a product and is based on applying the cold treatment of raw materials in the preparation of topinambour, freezing and low-temperature fine grinding followed by freeze drying. New technology allows to obtain additives from topinambour in the form of fine powders with a particle size dozens of times smaller than in the conventional grinding. Their quality in the content of fructose in the free state and BAS, withdrawn from the bound state, surpasses domestic and foreign counterparts. Comparison of the amino acid composition of proteins in the free and bound state in the original inulin-containing raw materials (freeze-dried topinambour) and nanopowders from topinambour was performed. It was found that in comparison with initial raw materials, in the fine grinding of frozen inulin-containing raw materials there is a significant mechanical destruction of protein molecules to individual amino acids, their transition from the bound state to the free state. Thus, in nanopowders from topinambour, the mass fraction of bound amino acids decreases twofold in comparison with the initial raw materials. At the same time, there is the 1,7-10-fold increase in the mass fraction of amino acids, which are in the free state.